التزام المتدخل الاقتصادي بضمان أمن المنتوجات - غمام جريدي, مليكة (Universty of Eloued جامعة الشهيد حمة الأخضر, 2022)
الملخص: من أجل تجسيد وتعزيز الحماية العالية الكفيلة المنتظرة شرعا للمستهلك في مجال ضمان أمن المنتوجات أولى المشرع الجزائري اهتماما خاصا بموجب قانون حماية المستهلك وقمع الغش 09-03 واتبعه بجانب تطبيقي هام، في المرسوم التنفيذي رقم 12-203 الذي تولى تحديد القواعد المطبقة في مجال أمن المنتوجات، حيث استحدث مجموعة من القواعد والضوابط القانونية ذات الطابع الوقائي تنظم عملية إنتاج وتداول المنتوجات، وفقا لمقاييس الأمن والسلامة المعتمدة، تتمثل في مجمل الالتزامات المفروضة على المتدخل الاقتصادي، والمتعلقة أساسا بالمطابقة والرقابة والإعلام والتحذير وتتبع مسار المنتوج...إلخ تتجسد في التزام واحد ألا وهو : "إلزامية أمن المنتوجات" ــ محل الدراسة ــ إلا أن تجسيد هذه القواعد والضوابط القانونية، وإن ساهمت حقيقة وبقدر كبير في الإنقاص من أخطار وأضرار المنتوجات، لكن لم تصل فعلا لوضع حد لها، فالمستهلك لازالت تترصده العديد من الأضرار والمخاطر، مما كان لازما على المشرع أن يدعم هذا التجسيد بفرض قيود تمتاز بالشدة في عملية العرض للاستهلاك، ترتب مسؤولية المتدخلين سوى المدنية أو الجزائية، مما يزيد من تفعيل الالتزام بالأمن. Abstract : Praise be to God, and prayers and peace be upon the one after whom there is no prophet, and after: This thesis is entitled "The Reality in the Arab Rhetorical Heritage on Firth's Contextual Theory - A Pragmatic Approach" The introductory dealt with general concepts about title, rhetoric and circulation, and in the first chapter: dealing with falsehood in the Arab rhetoric heritage, and it included three sections, the first usually in modern and heritage studies, the second: the grammatical context in modern and historical studies, and the third: semantics in modern studies, and the third: Perfumes and heritage, and in the second chapter: I dealt with justice in the Arab rhetorical heritage, and it included: The first of them: the non-linguistic in modern studies, and the second: the emergence of the non-linguistic in the Arab rhetorical heritage, where I dealt in counters: the non-linguistic elements in theory, and heritage With reference to the heritage origins contained in the instructions contained in the specific elements in Western theory, I dealt with the analysis of the most important elements in situations, situations such as the speaker, the addressee, time and place, biting speech and their value in building and understanding the text, and in the third chapter: a pragmatic approach between rhetorical heritage and Firth contextual theory And it included three basic topics, the first: the social component “Al Maqam”, the second: Situational Relationships and Arabic Rhetoric, and the third of them: the internal relationship, and “grammar”. Systematicism and Ecosystem Theory”, the current sentence, “the meanings of syntax and grammatical form”, the research appendix with a conclusion that notes the most important results, a list of sources and references, a list of foreign terms in the research, then an index of instructions for what the thesis contains.
أطروحة دكتوراه تخصص قانون خاص في العلوم السياسية
Keywords: الالتزام؛ الأمن؛ السلامة؛ المنتوج؛ المستهلك؛ المتدخل الاقتصادي؛ الخطر؛ الضرر؛ المطابقة؛ الرقابة؛ الإعلام؛ التحذير؛ تتبع مسار المنتوج؛ عرض المنتوج للاستهلاك؛ المسؤولية المدنية؛ المسؤولية الجزائية.; commitment; Security; safety; product; consumer; economic interventionist; danger; Harm ; conformity; censorship; media ; warning; product path tracking; product display for consumption; Civil responsibility ; Criminal liability.